The Expansion of the Mukhtasar Tawarikh Al-Wusta Theme in the Tempuling Poem and Preparation of Lesson Plans - Guntoro, Rinanda Setyanisa; Elmustian (Raja Zulkarnain Education Foundation, 2025)
This study aims to explore: 1) the central theme and supporting themes of the Mukhtasar Al Wusta hypogram text; 2) the theme of the transformation text of the Tempuling poem; 3) the expansion of the theme of the hypogram text in the transformation text; 4) the learning plan for the theme of the hypogram text using dual techniques through special teaching materials; 5) the learning plan for the theme of the transformation text using dual techniques through special teaching materials. This research took place in the odd semester of the 2024/2025 academic year using the library method. The research instrument was a checklist observation guideline. Data on the themes of the hypogram text and the transformation text were analyzed using an intertextuality approach, specifically focusing on the expansion aspect. The results of the study: 1) the central theme of the hypogram text is the national security because it is ruled by allying with a party that has powerr while the supporting theme-1 is the strategic location of the country is one of the reasons for the progress of a country and the supporting theme-2 is the leader and the people are united under the auspices of Islam; 2) the central theme of the transformation text is the fishermen's vigilance against the threat of disasters at sea, while the supporting theme-1 is fishermen who are persistent in saving themselves from the ferocity of the sea waves and the supporting theme-2 is the mental readiness of the family against disasters that fishermen may experience at sea; 3) the expansion of the theme of the hypogram text in the transformation text is in the aspect of the number of themes; 4) the learning plan for the theme of the hypogram text uses a dual technique through special teaching materials for the hypogram text involving 2 initial activities, 15 core activities, and 3 final activities; 5) the learning plan for the theme of the hypogram text using a dual technique through special teaching materials for the transformation text involving 14 core activities using special teaching materials.